Sustainable land use and climate adaptation: a review of European local plans - Zucaro, Floriana; Morosini, Rosa (TeMA - Journal of Land Use, Mobility and Environment, 2018)
Adaptation plans are the result of a political decision based on the awareness that climate change has altered environmental conditions and action is therefore needed in order to return to, maintain or achieve the desired outcome. A crucial role in defining adaptation actions is played by the use of resources, in particular of non-renewable resources such as soil. This paper, rooted on the reading of a sample of recent Italian and European adaptation plans, seeks to investigate the existence of environmental actions aimed at guaranteeing a sustainable use of natural and non-natural soil, in order to reduce the consumption of non-anthropized soil and also contribute to containing the effects of climate change. The paper is divided into three sections: the first one describes the methodology employed; the second one focuses on the most up-to- date plans regarding the effects of climate change in some urban systems; the third one proposes hints for further reflections and useful recommendations to local decision-makers in the development of tailor-made adaptation actions aimed at guaranteeing an efficient use of both natural and anthropized soil. The reading of the plans has exposed that soil consumption is not among the factors that need direct action to reduce the vulnerability of urban systems to current climate change, but rather it is a phenomenon that can be contained by increasing green areas and/or infrastructures and encouraging agricultural and environmental regeneration. The attention seems to be drawn to not yet sealed soil, thus leaving out the already anthropized one that, as such, would require, instead, greater adaptation efforts.